Pengembangan E-Joobsheet Berbasis Flip Pro pada Mata Kuliah Pembuatan Busana Wanita dan Anak Wanita - Sukmawaty, Wahyu Eka Priana; Nashikhah, Ma’rifatun (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This research aims to develop a flip pro-based e-job sheet for the course on Women's and Children's Clothing Design. The development is carried out through research and development (R&D) methods using the ADDIE model. The validation instrument is in the form of questionnaires/validation sheets for material, media, and language experts. The implementation instruments consist of learning outcome tests (pretest-posttest), student response questionnaires, and observations of learning activities—experts in material, media, and language conduct validation. Data analysis uses quantitative data analyzed descriptively (percentage, average score), while qualitative data from observations and interviews are analyzed to support quantitative findings The validation results indicate that the developed E-Jobsheet is highly suitable for use as a learning medium, with a very valid feasibility category. The implementation of E-Jobsheet in learning has proven to enhance students' learning outcomes in cognitive, affective, and psychomotor aspects, as well as receiving positive feedback from students. This media also helps students understand work procedures systematically, increases their learning independence, and can be adapted for various vocational materials. Thus, the Flip Pro-based E-Jobsheet effectively supports innovative and interactive learning of women's and children's fashion.